Generalized eruptive histiocytoma: case report - V. V. Chikin; L. F. Znamenskaja; A. JE. Karamova; V. A. Smol'jannikova; M. A. Nefedova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The case of generalized eruptive histiocytoma (GEH) in woman of 49 years old is reported. GEH is a rare disease relating to non-langerhans cell histiocytoses which are based on a benign reactive proliferation of histiocytes with immunophenotype inconsistent with Langerhans cells. As a result of treatment with methotrexate and betamethasone the improvement in skin condition was achieved.